A new approach to pollution modelling in models of the Environmental Kuznets Curve - Hannes Egli (ETH Zurich, CER-ETH - Center of Economic Research, 2005)
Models of the Environmental Kuznets Curve, particularly those with an ex- plicit abatement technology, often involve that pollution becomes negative in the long run. This, of course, is a highly implausible prediction. The paper at hand examines the problem of negative pollution by, rst, critically discussing two approaches adopted in existing EKC models and, second, by proposing a new approach. Motivated by the debatable assumption of perpetually increas- ing returns to scale in abatement, the idea of fading increasing returns to scale is introduced. This procedure does not only constitute a solution to the theo- retical problem of negative pollution, but also does well regarding the empirical plausibility of the abatement technology.
Keywords: Q2; Q5; 330; environmental Kuznets curve; negative pollution; abatement technology; increasing returns to scale; Umweltbelastung; Umweltschutz; Skalenertrag; Theorie; Environmental Kuznets Curve